KAIROMONAL EFFECT OF CORCYRA CEPHALONICA STAINTON AND THEIR INFLUENCE ON THE PARASITIC AND PREDATION POTENTIAL OF TRICHOGRAMMA CHILONIS ISHII AND CHRYSOPERLA ZASTROWI SILLEMI (ESBEN-PETERSON) AGAINST EGGS OF SPODOPTERA LITURA (FAB.) - P. PARTHIBAN,; C. CHINNIAH,; M. KALYANASUNDARAM, (The Bioscan, 2015)
The present study concentration (0.1 % = 1000 ppm) of the hexane extracts of male and female whole body and larval wash of host Corcyra cephalonica Stainton with Trichogramma chilonis Ishii and Chrysoperla zastrowi sillemi (Esben-Peterson) revealed their kairomonal activities under in vitro condition. Treating irradiated eggs of Spodoptera litura (Fab.) with hexane extract of adult female whole body of C. cephalonica (1000 ppm) recorded the parasitization of 13.24 per cent by T. chilonis on third day after inoculation which increase from 49.73 to 70.66 per cent on fifth and seventh day after inoculation and they were 5.14, 16.72 and 28.34 per cent when the eggs were treated with hexane alone on third, fifth and seventh days after inoculation, respectively. Maximum emergence (67.84%) was observed with C. cephalonica female whole body extract followed by male whole body extract (56.33%). The highest predation by C. zastrowi sillemi on hexane extract of C. cephalonica female whole body treated eggs of S. litura was recorded (69.14%) whereas it was 29.43 per cent in hexane treated eggs, these are the results shows that C. cephalonica female whole body having high kairomonic impact it may be used for future biological control programme.